Expressing environment assumptions and real-time requirements for a distributed embedded system with shared variables - Tjell, Simon (2008)
Apresentado na 6th IFIP TC10 Working Conference on Distributed and Parallel Embedded Systems (DIPES 2008), no âmbito do 20th IFIP World Computer Congress, Milão, Itália, set/2008.